Analyzing Spelling Errors in EFL Narrative Writing: Insights from Indonesian Junior High School Students - Putra, M. Yarza Abdi Yoan; Hanafi, Mohammad; Astutik, Yuni Muji (ICONELT, 2024)
Spelling is one of the most important aspects for EFL learners to master in order to achieve good competence in writing. However, many learners still struggle with English spelling accuracy, which often results in errors. Analyzing students’ errors is essential to understand their learning problems and needs. Hence, this study is aimed at analyzing and finding out the types of spelling errors and the most frequent type of spelling error in students’ narrative writing at one of the junior high schools in an Indonesian EFL setting using the classification of Bestgen and Granger (2011) to extend knowledge from the previous literature. This study employed a descriptive qualitative approach, with tests and documentation serving as the data collection technique. Using purposive sampling, 73 students’ narrative writings were analyzed, and it was found that students made nine types of spelling errors. The types were: omission of letter, addition of letter, single letter instead of double letter, double letter instead of single letter, substitution of letter, interchange of two adjacent letters, error involving an apostrophe, segmentation error, and multiple errors. It was also found that the most frequent type of spelling error was omission of letter, contributing to 21.1% of the errors. From the errors, possible factors of students’ spelling errors were also discussed. The errors show that students still struggle with English writing, especially spelling. Therefore, students need more practice and regular exposure to English writing, while educators should ensure that spelling receives adequate emphasis in classroom instruction and materials.